An employee's best friend? How AI can boost employee engagement and performance. Issue 1 (11th February 2019) - Smith, Cameron
Abstract : Purpose: How to keep employees engaged, rewarded and retained to improve the end-user and customer experience. Design/methodology/approach: This study provides practical advice on how a business can attract, recruit, retain and develop talented employees to improve customer service, using the author's experience at Genesys. Findings: This study explores various research findings including Coleman Parks to establish the challenges organizations face when trying to ensure employees are engaged with their own business. Originality/value: This is my viewpoint on the situation; I have researched various areas of employee engagement to understand why organizations are facing challenges, and I can provide unique insight as we work with world-leading brands to use technology that will solve these problems in some way at the least.